The effect of retail packaging method on objective and consumer assessment of beef quality traits. (June 2015) - Geesink, Geert; Robertson, Joanna; Ball, Alex
Abstract: This study evaluated the effect of 7 days of modified atmosphere packaging (MAP: 80% O2, 20% CO2 ) or skin packaging (no oxygen) of beef M. longissimus steaks after 1 or 7 days of ageing in vacuum on objective and sensory meat quality traits and degradation of desmin. Shear force was negatively affected by MAP after both 1 and 7 days of ageing in vacuum ( P < 0.005). Sensory evaluation of grilled steaks revealed significantly negative effects of MAP on sensory traits, resulting in an overall decrease of 8 points in the Meat Standards Australia (MSA) eating quality score (MQ4). Desmin degradation was not affected by packaging method, suggesting that the toughening effect of high-oxygen MAP is not due to inhibition of postmortem proteolysis. The results of this study and others suggest that packaging method should be incorporated as a variable in the MSA grading system. Further research to quantify the impact of oxidative cross-linking of proteins on tenderness appears warranted.